2013
DOI: 10.1105/tpc.113.116343
|View full text |Cite
|
Sign up to set email alerts
|

bZIP67 Regulates the Omega-3 Fatty Acid Content of Arabidopsis Seed Oil by Activating FATTY ACID DESATURASE3    

Abstract: Arabidopsis thaliana seed maturation is accompanied by the deposition of storage oil, rich in the essential v-3 polyunsaturated fatty acid a-linolenic acid (ALA). The synthesis of ALA is highly responsive to the level of FATTY ACID DESATURASE3 (FAD3) expression, which is strongly upregulated during embryogenesis. By screening mutants in LEAFY COTYLEDON1 (LEC1)-inducible transcription factors using fatty acid profiling, we identified two mutants (lec1-like and bzip67) with a seed lipid phenotype. Both mutants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
155
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(162 citation statements)
references
References 61 publications
7
155
0
Order By: Relevance
“…A de novo motif search showed that two motifs, the G-boxcontaining motif and the CCAAT box motif, are overrepresented in putative LEC1 target genes . However, disruption of the G-box but not the CCAAT box abolished the activation of seed storage-related genes by NF-YC2/bZIP67/LEC1 (or L1L) in mesophyll protoplasts (Yamamoto et al, 2009;Mendes et al, 2013). In this study, we demonstrate that the association with the G-box via PIFs is necessary for LEC1 to promote the expression of genes in response to skotomorphogenic growth.…”
Section: Discussionmentioning
confidence: 60%
“…A de novo motif search showed that two motifs, the G-boxcontaining motif and the CCAAT box motif, are overrepresented in putative LEC1 target genes . However, disruption of the G-box but not the CCAAT box abolished the activation of seed storage-related genes by NF-YC2/bZIP67/LEC1 (or L1L) in mesophyll protoplasts (Yamamoto et al, 2009;Mendes et al, 2013). In this study, we demonstrate that the association with the G-box via PIFs is necessary for LEC1 to promote the expression of genes in response to skotomorphogenic growth.…”
Section: Discussionmentioning
confidence: 60%
“…DEs were derived from fatty acid profiles in a manner similar to that of Botella et al (2016) using the following calculations: v-6 DE = 18:2 + 18:3/18:1 + 18:2 + 18:3 and v-3 DE = 18:3/18:2 + 18:3. Lipid extracts also were analyzed by electrospray-tandem mass spectrometry using an ABSiex 4000 QTRAP system as described previously (Mendes et al, 2013).…”
mentioning
confidence: 99%
“…DNase-treated RNA was purified from seeds using the RNeasy kit from Qiagen with modifications described previously (Mendes et al, 2013). Single-stranded cDNA synthesis was carried out using SuperScript II RNase H 2 reverse transcriptase from Invitrogen.…”
mentioning
confidence: 99%
“…Loss of GL2 activity in the seed coat, rather than the embryo, produces the high seed oil phenotype, partially by influencing MUCILAGE MODIFIED4 expression, which promotes mucilage biosynthesis in the seed coat (Shi et al, 2012). bZIP67 regulates seed a-linolenic acid content by binding G-boxes in the FATTY ACID DESATURASE3 (FAD3) promoter (Mendes et al, 2013). TRANSPARENT TESTA8 (TT8) inhibits seed FA accumulation by targeting LEC1, LEC2, and FUS3 in the seeds .…”
mentioning
confidence: 99%